2010
DOI: 10.5483/bmbrep.2010.43.10.664
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemopreventive effects of Thymoquinone on cell surface glycoconjugates and cytokeratin expression during DMBA induced hamster buccal pouch carcinogenesis

Abstract: The present study aimed to investigate the membrane stabilizing effect of Thymoquinone (TQ) on cell surface glycoconjugates and cytokeratin expression against DMBA induced hamster buccal pouch carcinogenesis. 0.5% DMBA painting (three times per week) in hamster buccal pouches for 14 weeks resulted in the formation of well developed oral squamous cell carcinoma. We observed 100% tumor formation with marked abnormalities of glycoconjugates status in tumor bearing hamsters as compared to control animals. Oral adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Glucose, galactose, fucose, mannose, sialic acid and some acetylated derivatives of hexosamine are the main sugar moieties in glycoproteins. Being an important constituent of cell membrane, glycoconjugates plays an essential role in cell function and cell membrane functions [52]. The elevation of glycoconjugates in circulation has been reported to happen via increased turn over, secretion and/or shedding from damaged/malignant cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose, galactose, fucose, mannose, sialic acid and some acetylated derivatives of hexosamine are the main sugar moieties in glycoproteins. Being an important constituent of cell membrane, glycoconjugates plays an essential role in cell function and cell membrane functions [52]. The elevation of glycoconjugates in circulation has been reported to happen via increased turn over, secretion and/or shedding from damaged/malignant cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of Nigella sativa seed extract enriched with TQ suppressed mice skin papillomagenesis when applied topicall (Salomi et al, 1991). In a similar fashion, 7,12-dimethylbenz[a]anthracene DMBA-induced hamster buccal squamous cell carcinoma burden was lessened when TQ was administered by gavage (Rajkamal et al, 2010). A significant attenuation has been reported in breast, gastric, and colon cancer xenografts after intra peritoneal administration of TQ (Gali-Muhtasib et al, 2008; Lei et al, 2012; Woo et al, 2013).…”
Section: Chemo-potentiating Role Of Tqmentioning
confidence: 93%
“…Although only a few studies have been performed on the effect of TQ on oral cancer, it is still promising. 60 , 63 , 64 A study by Chu et al 60 revealed that the treatment of human oral cancer with TQ induces cell death by the 2 distinct mechanisms of apoptosis and autophagy. Apoptosis is programmed cell death.…”
Section: Oral Cancermentioning
confidence: 99%
“… 67 , 68 Only one oral cancer prevention study through the use of TQ has been published. 63 They used 7,12 dimethyl benz (a) anthracene (DMBA) in an induced hamster buccal pouch carcinogenesis model to study TQ chemoprevention. The DMBA is known to induce multistep carcinogenesis.…”
Section: Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation